THE USE OF MODERN INFORMATION TECHNOLOGY IN TEACHING ELECTRONICS - Ptak, Paweł; Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper presents systems created in the software environment are tested in terms of operation and the operating parameters. The testing also includes the faithfulness of representing the actual circuit operation. Students work with these circuits during laboratory classes of Introduction to Electronics. The results of measurements obtained during the classes are compared with the results obtained by students when working with simulated electronic circuits. The results of students’work carried out with the two methods were assessed.